Quality Measurement of HIV Care Service for People Living with HIV and AIDS in Thailand - เลิศพิริยสุวัฒน์ ชีวนันท์; เรืองชัย ศรีลัย; เสถบุตร ชื่นกมล; ฟักทองคำ กาญจนา; ภาวนาภรณ์ วิภา (Disease Control Journal, 2012)
The project entitled "Model development of quality improvement (QI) of HIV care service forpeople living with HIV and AIDS" has been initiated since 2001. This study aimed to compile informationon its development and to demonstrate the results of QI measurement at national level during 2005-2010using HIVQUAL-T and Pediatric HIVQUAL-T software.The project resulted in the expansion of the implementation to nationwide government hospitals, establishmentof steering committees on quality improvement (QI) of HIV care in regional and provincial levels and improvement of measurement software. In 2010, 355 trainers on QI were trained. In monitoring of theperformance, as shown in most indicators, increasing trends of service coverage were indicated. As for 2010alone, data were analyzed based on 49,559 adult patients from 748 hospitals and 3,418 pediatric cases.Almost all indicators had scores of 80%, except for CA cervix screening (70.0%); primary prophylaxis forPenicilliosis (43.4%) and for MAC (25.6%); and HIV disclosure to child (74.5%). A few indicatorsaddressing pediatric care including TB screening, developmental assessment and immunization assessment,showed minor declining trend which might cause by the effect of enrollment of new hospitals to the project.We recommend that implementation of QI project and its performance measurement by indicators should becontinued. To support for project sustainability, network of implementing agencies at every level should befocused and strengthened. Linkage of HIV QI project with hospital accreditation should be promoted.